2016
DOI: 10.1021/acs.jnatprod.5b01091
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotiamide: The First Non-Peptide-Based Natural Product Activator of Bacterial Caseinolytic Protease P

Abstract: Caseinolytic protease P (ClpP) maintains essential roles in bacterial homeostasis. As such, both the inhibition and activation of this enzyme result in bactericidal activity, making ClpP a promising target for antibacterial drug development. Herein, we report the results of a fluorescence-based screen of ~450 structurally diverse fungal and bacterial secondary metabolites. Sclerotiamide (1), a paraherquamide-related indolinone, was identified as the first non-peptide-based natural product activator of ClpP. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…For example, imipridone-based anti-cancer therapy might adversely impact the microbiome or, conversely, the use of imipridones as antibiotics might negatively impact normal tissues that require high mitochondrial capacity. A number of compounds have been identified as ClpP activators, including the ADEPs and a variety of (semi)-synthetic analogs (Brötz-Oesterhelt et al 2005;Carney et al 2014b;Goodreid et al 2016;Wong et al 2018;Griffith et al 2019), ADEP-based fragments (Carney et al 2014a), the imipridones and the related TR series compounds (Allen et al 2013;Graves et al 2019;Ishizawa et al 2019;Wong and Houry 2019), the natural product sclerotiamide (Lavey et al 2016), and the synthetic compounds D9 (Stahl et al 2018) and ACP1 (Leung et al 2011). X-ray structures show that ONC201, ADEPs, and D9 all occupy the same binding site in human CLPP (Stahl et al 2018;Wong et al 2018;Ishizawa et al 2019;Wong and Houry 2019).…”
Section: Species-specific Activators Of Clppmentioning
confidence: 99%
“…For example, imipridone-based anti-cancer therapy might adversely impact the microbiome or, conversely, the use of imipridones as antibiotics might negatively impact normal tissues that require high mitochondrial capacity. A number of compounds have been identified as ClpP activators, including the ADEPs and a variety of (semi)-synthetic analogs (Brötz-Oesterhelt et al 2005;Carney et al 2014b;Goodreid et al 2016;Wong et al 2018;Griffith et al 2019), ADEP-based fragments (Carney et al 2014a), the imipridones and the related TR series compounds (Allen et al 2013;Graves et al 2019;Ishizawa et al 2019;Wong and Houry 2019), the natural product sclerotiamide (Lavey et al 2016), and the synthetic compounds D9 (Stahl et al 2018) and ACP1 (Leung et al 2011). X-ray structures show that ONC201, ADEPs, and D9 all occupy the same binding site in human CLPP (Stahl et al 2018;Wong et al 2018;Ishizawa et al 2019;Wong and Houry 2019).…”
Section: Species-specific Activators Of Clppmentioning
confidence: 99%
“…65,68 Both identified small-molecule activators of E. coli ClpP by using an in vitro assay measuring increases in fluorescence caused by cleavage of fluorescein isothiocyanate-casein, a model substrate for ClpP. In the first, Leung et al 65 screened 60 000 drug-like synthetic chemicals, identifying five compounds termed ACP1-5 ( Figure 4a).…”
Section: Clpp Activatorsmentioning
confidence: 99%
“…The most active of these compounds were 10-20-fold less potent than ADEP1 at activating ClpP and only displayed modest antibacterial activity even in the presence of permeabilizing agents. Lavey et al 68 instead screened 420 450 fungal and bacterial extracts or metabolites and identified a single ClpP activator, sclerotiamide (Figure 4a). This paraherquamide-related indolinone was 73-fold less potent than ADEP1 at activating EcClpP and failed to inhibit growth of efflux deficient E. coli or Pseudomonas aeruginosa.…”
Section: Clpp Activatorsmentioning
confidence: 99%
“…A non-peptide-based natural product activator of ClpP, sclerotiamide, has recently been identied in a screening for bcasein degradation. 95 As of yet, there is no available data on neither the mechanism of ClpP binding nor antibacterial activity of this compound. In comparison to the natural product ADEP1, casein degradation was slow and rather high concentrations of sclerotiamide were required.…”
Section: Uncontrolled Clpp Activity Is Bactericidalmentioning
confidence: 99%